P609 Impact of accessibility of medical care and socioeconomic class on outcomes of IBD – a nationwide population study. (27th May 2021) - Ledder, O; Harel, S; Orlanski-Meyer, E; Yogev, D; Loewenberg Weisband, Y; Greenfeld, S; Kariv, R; Lederman, N; Matz, E; Schwartz, D; Focht, G; Dotan, I; et al.
Abstract: Background: Despite ongoing improvements in Inflammatory Bowel Disease (IBD) therapeutics, timely access to quality medical care likely impacts patient outcomes. Physical distance from specialty care and socioeconomic status (SES) may impact quality of care. In a nationwide population study we aimed to assess the impact of patient location and SES on IBD outcomes. Methods: This Epi-IIRN project utilized a meta-database incorporating patient data of all four health maintenance organisations (HMO) in Israel, representing 98% of the population. All patients identified on the incidence cohort were followed from diagnosis until end of 2018. Regions in Israel were defined as central (coastal plain and Jerusalem corridor), northern region and southern region. SES class were defined by postcode as per Israel bureau of statistics data from SES 1 (lowest) to SES 4 (highest). Primary outcome was steroid dependency, with secondary outcomes of biologic therapy use during first year of diagnosis, surgery, gastroenterology visits, hospitalizations and mortality. Analysis was performed separately for Crohn's disease (CD) and ulcerative colitis (UC). Results: A total of 30, 167 IBD patients (16, 936 (56%) CD and 13, 231 (44%) UC) were included: 74% of patients were in central region, 12% southern region and 14% northern region. 21% were in SES class 1 and 12% in SES 4. In CD, lower SES was associated with higher steroid dependency (37% vs 30%, p=0.002), higher surgery rates (21% vs 12%, p<0.001), more hospitalizations (2.4 vs 1.1, p<0.001), more emergency department (ER) visits (2.9 vs 1.9, p<0.001) and higher mortality (3.3% vs 2.5%, p=0.03). Regarding region, steroid dependency, hospitalization rate, ER visits and surgery rate were all lower in central regions compared to both northern and southern region (p<0.001 for both central vs northern, and central vs southern regions). Similarly, gastrointestinal specialized clinic visits were more frequent in central regions (p=0.01). In UC, lower SES was associated with lower frequency of gastrointestinal clinic visits (5.0 vs 8.5, p<0.001). This was associated with more hospitalizations (1.6 vs 0.7, p<0.001), ER visits (2.1 vs 1.6, p=0.002), surgeries (7.6% vs 5.0%, p=0.014) and higher mortality (5.1% vs 4.2%, p=0.026). By region, gastrointestinal clinic visits were more frequent, and ER visits, hospitalizations (all p<0.001) and surgeries (p=0.001) were all lower in central compared to both northern and southern regions. Conclusion: In this nationwide analysis we show deleterious impact of both lower SES and peripheral residence on outcomes of CD and UC. Policy makers should consider these data to facilitate improved access to medical care and maximize IBD outcomes in a standardized way.